تأثير الحوكمة الرشيدة على مخاطر الائتمان في البنوك الإسلامية: دراسة حول دول مجلس التعاون الخليجي - Salhi, Bassem (مجلة العلوم الإدارية و الإقتصادية, 2018)
This article aims to determine the relationship between factors of governance and the level of risk in 27 Islamic Golf banks in cooperation with countries (Saudi Arabia, Oman, Kuwait, Bahrain, the United Arab Emirates and Qatar) from 2008-2015. The important empirical question is: do internal mechanisms of governance, e.g., the formation of a board, contribute to the reduction of financial risks, such as credit risks, by Islamic banks specifically located in Gulf countries? The estimates in this paper are produced by a single-equation model that connects the variables related to governance with credit risk as it impacts the banks’ finances. In the first phase of the analysis, our empirical approach tests the impact of each exogenous variable studied on the reduction of bank credit risk in Islamic banks. We also undertake a second phase of multivariate analysis in which the controlled simultaneous effect of all the variables on the endogenous variable is studied. Results show that internal governance mechanisms regulated by a board have diverging effects on the financial risk of Islamic banks in selected examples, particularly on credit risk.